TINJAUAN HUKUM PEMENUHAN UANG KOMPENSASI DAN GANTI RUGI DALAM PERJANJIAN KERJA WAKTU TERTENTU (PKWT) BERDASARKAN UNDANG-UNDANG CIPTA KERJA - Jenita Tan; Gunardi Lie (Jurnal Riset Multidisiplin Edukasi, 2026)
A Fixed-Term Employment Agreement (PKWT) is a type of employment contract explicitly regulated under Indonesian labor law. Following the enactment of Law Number 11 of 2020 concerning Job Creation and its related regulations, including Government Regulation Number 35 of 2021, additional provisions have been established regarding the obligation to provide compensation and damages to PKWT workers/laborers. This study aims to examine the legal provisions concerning the granting of compensation and damages in PKWT in accordance with the Job Creation Law. The methodology used is normative legal research, employing both statutory and conceptual approaches. The results of the study indicate that the Job Creation Law requires employers to provide compensation at the end of a PKWT based on the duration of employment and obliges the payment of damages if either party terminates the PKWT before the agreed contract period expires. The implementation of this regulation continues to face obstacles due to the lack of legal awareness among employers and the insufficient supervisory measures.